Mixed convection stagnation-point flow over a vertical plate with prescribed heat flux embedded in a porous medium: Brinkman-Extended Darcy formulation. - Rosali, Haliza; Ishak, Anuar; Pop, Ioan (Springer Link, 2011)
This article considers the problem of mixed convection stagnation-point flow towards a vertical plate embedded in a porous medium with prescribed surface heat flux. It is assumed that the free stream velocity and the surface heat flux vary linearly from the stagnation point. Using a similarity transformation, the governing system of partial differential equations is transformed into a system of ordinary differential equations, before being solved numerically by a finite-difference method. The features of the flow and the heat transfer characteristics are analyzed and discussed. It is found that dual solutions exist for both buoyancy assisting and opposing flows.